The Development of Learning Instrument Science-Biology for Junior High School at Class VIII with Guided Inquiry Model of Character Education Integrated - Fatimah, Siti; Prahatamaputra, Aminuddin (Universitas Sebelas Maret, 2015)
This study aims to generate learning instrument of science-biology with model guided inquiry of character education integrated at plant physiology process concept at class VIII for junior high school that valid, practical, and effective. The development learning instrument of science biology uses method research and development (R & D) which refers to the model of the software development phases: 1) analysis of students learning styles, 2) formulate learning objectives, 3) selecting appropriate media, 4) use of media and instructional materials, 5) developing activity students, 6) evaluation and revision, and 7) implementation. Learning instrument include; the syllabus, lesson plan, student worksheets, instructional materials, and test results of learning. The results of research as follows: 1) The results of the assessment validator indicate learning instrument is valid with both categories; 2) small group evolution test results meet the practical criteria; 3) implementation of the model of guided inquiry character education integrated meets the criteria effective, namely: a) the result of a very good learning management, b) the response of students classified as positive. c) educational assessment meets the criteria of good character; d) the activity of students in the high category; e) results of tests of learning outcomes achieve minimum completeness, and f) motivation to learn a positive effect on student achievement. Based on these results it can be concluded that the development learning instrument science-biology using the model guided inquiry of character education integrated is valid, practical, and effective.Keywords: Science-biology learning for junior high school, guided inquiry, character education